PENGARUH BEAUTY VLOGGER TERHADAP MINAT BELI PRODUK KOSMETIK WARDAH DENGAN CITRA MEREK SEBAGAI VARIABEL MEDIASI (Survei Pada Mahasiswi Universitas Slamet Riyadi Surakarta) - Edi Wibowo, Sunarti,; Sri Utami, Setyaningsih (Universitas Slamet Riyadi, 2018)
The purpose of this study is to analyze 1) the effect of beauty vlogger as e-WOM on brand image; 2) the influence of beauty vlogger as e-WOM on purchase intention; 3) the influence of brand image on purchase intention; and 4) the influence of beauty vlogger as e-WOM on purchase intention through brand image. This research was conducted at the students of Slamet Riyadi University, Surakarta. The sample size taken was 70 respondents, with non-probability sampling method and purposive sampling using path analysis. Based on the analysis, it was found that the beauty vlogger as e-WOM had a significant effect on brand image, beauty vlogger as e-WOM had a significant effect on buying interest, brand image had a significant effect on purchase intention, brand image mediates the influence of beauty vlogger as e-WOM on purchase intention. Based on the results of the research, the use of beauty vlogger must be decided appropriately in order to have a very large influence on the level of product salesKeywords: Beauty Vlogger, e-WOM, Brand Image, Purchase Intention.